Lima Pendekatan dalam Penelitian Kualitatif - Werdiningsih, Endang; B, Abdul Hamid (FKIP Universitas Wisnuwardhana, 2022)
Qualitative research is research in a natural setting and researchers are directly involved in it. Research is descriptive, paying more attention to the process than the results. The language of this research is empirical. Data analysis is done inductively, and meaning is essential. In the study of social sciences, qualitative research has several types of approaches which are described in detail as follows: (1) narrative research, (2) phenomenology, (3) grounded theory, (4) ethnography, and (5) case study. Each approach is described from the definition, history, types, how to use it, advantages and challenges. The similarities and differences between the five approaches are also described.